Metacognitive skill profile of biology education students at institute of teachers’ education in South Sulawesi, Indonesia - Romi Adiansyah; Astuti Muh. Amin; A. Ardianto; Ahmad Yani (University of Muhammadiyah Malang, 2022)
Metacognitive skills are one of the abilities required in the twenty-first century, to achieve independent learning. However, these skills still need to review whether these skills have been empowered by educators, particularly in universities. This research was aimed at determining the metacognitive skill profile of Biology Education students at the Institute of Teachers’ Education in South Sulawesi, Indonesia. This research used a descriptive quantitative method. The population of this research was all the students of the Biology Education Study Program at the non-state Institute of Teachers’ Education in South Sulawesi. The samples of this research were 356 Biology Education students in the second semester who programmed the Environmental Science course in the 2020/2021 academic year. The instrument used in this research was an essay test to measure students’ metacognitive skills in the Environmental Science course. The results of the data analysis indicate that the students’ metacognitive skills are in the category of undeveloped as much as 89.27%. Therefore, some efforts to improve students’ metacognitive skills are required by those institutes through the implementation of a learning model which can empower the metacognitive skills of the prospective Biology teacher students.